Anticancer and antioxidant activity of clinacanthus nutans active fractions - Khairun Najwa binti Zakaria (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Today, there are many chemotherapy drugs that have been used to treat cancer patients. However, those drugs usually give adverse side effects on human health. Therefore, this research sought to explore the therapeutic potential of Clinacanthus nutans (C.nutans) leaves extract on liver cancer. C.nutans leaves extract was assessed on its potential as an antioxidant and anti-cancer agent by studying their response to scavenge DPPH free radical and its effect on Hep-G2 liver cancer cells growth. At first, the methanol extraction was carried out followed by partial purification. Partial purification was started by applying Thin Layer Chromatography (TLC) technique to identify the best mobile phase to be used in the open chromatography technique. Four spots were observed on the TLC plate when hexane: ethyl acetate with ratio 7:3 was applied as the mobile phase. Then, all four active fractions were collected in the bigger amount using column chromatography using the same mobile phase. Later, phytochemical screening was carried out to preliminary identify the type of compounds extracted. Antioxidant activity of the collected fractions was then investigated using DPPH assay. BHT, a known antioxidant agent was used as the positive control. The active fraction F1 recorded the highest percentage in scavenging activity (38.8 %) at 200 g/ml, while the other C.nutans active fractions F2, F3, and F4 scavenged DPPH activity at 37.1 %, 35.2 % and 38.4 %, respectively. After that, the effect of the isolated fractions on Hep-G2 liver cancer cells growth was observed by MTT assay. The assay was used to indicate the C.nutans leaves extract half maximal inhibitory concentration (IC50). The active fraction F2 was chosen for further experiment as it gave the lowest IC50 value against MTT assay. The effects of active fraction F2 on Hep-G2 liver cancer cells were further scrutinized by the growth kinetic study to forecast its ability in eradicating the growth of cancer cells. F2 gave significant effect on Hep-G2 liver cancer cells with an IC50 value of 1.73 g/ml. During the phytochemical screening, F2 showed a presence of triterpenes that could be responsible for the anti-proliferative activity. Furthermore, the growth kinetics study indicated that F2 active fraction inhibited the cell growth with the number of cell generation reduced from 3.86 to 3.74 generations. Active fraction F2 had also affected the growth rate with dynamical decrement from 0.0086 h-1 to 0.0079 h-1 as compared to untreated Hep-G2 cells which only declined at a rate of 0.0037 h-1. In conclusion, it can be considered that among the four isolated active fractions, active fraction F1 showed better in antioxidant activity while active fraction F2 is good as anticancer agent.